Pregnancy in the Cardiac Catheterization Laboratory: A Safe and Feasible Endeavor. (April 2021) - Cheney, Amy E.; Vincent, Logan L.; McCabe, James M.; Kearney, Kathleen E.
Abstract : Concerns over radiation exposure are ubiquitous to all interventional cardiologists; however, fear of exposure during childbearing years disproportionately deters women from entering the field. This review summarizes the available data on occupational radiation exposure during pregnancy with an emphasis on radiation quantification, the impact of exposure at various stages of fetal development, societal recommendations for safe levels of exposure during gestation, threshold levels necessary to induce fetal harm, and safe practices for the pregnant interventionalist. Reconciling the available information, we conclude that pregnancy in the cardiac catheterization laboratory is both safe and feasible. This review also highlights new technologies that may augment standard radiation safety techniques and are of particular interest to the pregnant interventional cardiologist. Finally, we propose steps to improve female representation in this field, underscoring the importance of a sex-balanced workforce.